Farmer Jack talks about what he learned from community session - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) gender team visited Lower Kamula village in Western Kenya to test an upcoming Practitioner's Guide for gender and social research. The session in Lower Kamula village that was tested was 'Co-appreciation'. It encourages participants to think about their own strengths what the village has in terms of values and resources, and what it needs to prosper. Part of the session is also to elaborate on pathways to achieve the various goals that the community sets out. Learn more about our work: www.ccafs.cgiar.org/gender